Pengaruh Model Pembelajaran Role Playing Terhadap Pemahaman Materi Kebudayaan dalam Pelajaran IPS Kelas VIII SMP Negeri 2 Botomuzoi TP.2024/2025 - Agus Candra Lahagu; Wahyutra Adilman Telaumbanua; Yearning Harefa; Bezisokhi laoli (Universitas Negeri Medan, 2025)
This study aims to determine the effect of the Role Playing learning model on students’ understanding of cultural material in Integrated Social Studies (IPS) for Grade VIII at SMP Negeri 2 Botomuzoi in the 2024/2025 academic year. The background of this research is the low student achievement in cultural topics, due to the use of conventional learning methods that do not actively involve students. This research employed a quantitative approach using a pre-experimental design of the one group pretest-posttest type, without a control group. The sample consisted of 18 students from class VIII-A. The instrument used was an essay-based learning achievement test administered before and after the treatment. The results showed an increase in the average score from 47.11 (pre-test) to 85.22 (post-test). The Paired Sample t-Test yielded a significance value of 0.000 (p < 0.05), indicating a significant effect of the Role Playing model on students’ learning outcomes. Additionally, this model enhanced student engagement, motivation, and understanding of cultural concepts. Therefore, the Role Playing learning model is proven to be effective in improving students’ learning outcomes in social studies, particularly in cultural material, and is recommended as an alternative active learning strategy.